Toward a General and Unified View of Educational Research and Evaluation - Rocco J. Perla; James Carifio (The Evaluation Center at Western Michigan University, 2009)
This paper addresses an important problem that may really be a pseudoproblem perpetuated by a current artificial or even political need to isolate researchers, evaluators, and theorists and put them in conceptual-methodological boxes. In this paper, we argue that scholars of all kinds should focus on the nouns (i.e., research, evaluation, theory) versus the adjectives (i.e., quantitative, qualitative, or mixed methods) used to qualify these nouns and core constructs. In a word, researchers, evaluators, measurement professionals, and theorists of all persuasions should strive to be neither qualitative nor quantitative, as that is like striving to be a single leg in a triangle. Following Hacking (1965), our view is that all forms of research methodology and evaluation methodology represent a "patchwork quilt" that is essentially "one fabric" with two connected but often unacknowledged sides to the quilt and that all methodology, analysis, and evaluations are essentially "qual-quantification" and "quant-qualification" and usually both at the same time. This general and unified or "one fabric" view of these debates and issues is discussed from a historical-philosophical perspective, and the need for a more general and inclusive evaluation and research epistemology is elucidated. Having outlined an epistemic framework and argument for a more comprehensive and complete view and model of evaluation and research that transcends a specific research paradigm, the paper concludes by outlining eight general key points that most (if not all) researchers and evaluators should consider.